2007
DOI: 10.1080/17470910701399029
|View full text |Cite
|
Sign up to set email alerts
|

Aging, self-referencing, and medial prefrontal cortex

Abstract: The lateral prefrontal cortex undergoes both structural and functional changes with healthy aging. In contrast, there is little structural change in the medial prefrontal cortex, but relatively little is known about the functional changes to this region with age. Using an event-related fMRI design, we investigated the response of medial prefrontal cortex during self-referencing in order to compare age groups on a task that young and elderly perform similarly and that is known to actively engage the region in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
143
9
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(169 citation statements)
references
References 63 publications
16
143
9
1
Order By: Relevance
“…More interestingly, there were also differences in activations between the two types of semantic judgments, with judgments about the self leading to greater activation in the MPFC than judgments about the other. An increased activation in the MPFC when reflecting on one's own traits (compared to the traits of others or to making semantic judgments) has also been observed in several subsequent studies [14][15][16][17][18][19][20][21][22][23][24][25][26] (see Fig. 1 for an illustration of the MPFC activations detected in different studies).…”
Section: Representing One's Personal Characteristics: Semantic Forms mentioning
confidence: 86%
See 1 more Smart Citation
“…More interestingly, there were also differences in activations between the two types of semantic judgments, with judgments about the self leading to greater activation in the MPFC than judgments about the other. An increased activation in the MPFC when reflecting on one's own traits (compared to the traits of others or to making semantic judgments) has also been observed in several subsequent studies [14][15][16][17][18][19][20][21][22][23][24][25][26] (see Fig. 1 for an illustration of the MPFC activations detected in different studies).…”
Section: Representing One's Personal Characteristics: Semantic Forms mentioning
confidence: 86%
“…White circles represent the locations of peak MPFC activations detected when reflecting on one's own psychological traits relative to reflecting on the traits of others or making semantic judgements. [13][14][15][16][17][18][19][20][21][22][23]25,26,29,30 White squares represent the locations of peak MPFC activations detected when reflecting on one's own promotion goals. [38][39][40][41] when participants made judgments from their own perspective and when they made judgments from the perspective of their friend.…”
Section: Representing One's Personal Characteristics: Semantic Forms mentioning
confidence: 99%
“…Thus, when people are asked to process information in a self-relevant manner (e.g., deciding whether adjectives describe them), activity in the VMPFC is greater than in conditions in which people process information in reference to others (e.g., deciding whether adjectives describe President Bush; Johnson et al, 2002;Schmitz, Kawahara-Baccus, & Johnson, 2004). This tie between VMPFC activity and self-referential processing occurs for older adults as well as for young adults (Gutchess et al, 2007). In fact, this tie between MPFC activity and self-referential processing may explain the belowbaseline response shown in this task, as in most prior studies examining MPFC response (e.g., D'Argembeau et al, 2005;Johnson et al, 2005;Kensinger & Schacter, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, the directionality of these PFC changes is not clear. Some studies have revealed overrecruitment of PFC processes in older adults during the processing of negative affect (e.g., Gunning-Dixon et al, 2003;Tessitore et al, 2005;Williams et al, 2006), whereas other studies have found that older adults underrecruit the PFC during the processing of negative information (e.g., Gutchess et al, 2007;Samanez-Larkin et al, 2007). Because few studies have compared young and older adults' processing of positive and negative information equated on arousal (most have compared fearful with happy facial expressions, where happy expressions are likely to be lower in arousal), a likely contributor to these contradictory findings is the confluence of arousal-based and valence-based processes.…”
mentioning
confidence: 99%
“…A recent study demonstrated that this region is functionally intact in healthy older adults during self-referential tasks. 50 As such, it is possible that the high concussion group might be relying more heavily on selfreferential processing to successfully retrieve intact relational pairs from impairments in regions that typically subserve relational memory processes.…”
Section: Figmentioning
confidence: 99%